INFLUENCE OF PERCEIVED USEFULNESS AND EASE OF USE ON STUDENTS’ CONTINUOUS INTENTION IN LEARNING ON-LINE ENGLISH LESSONS: AN EXTENDED TAM - Akmal Akmal (UAD TEFL International Conference)
There are huge numbers of English lessons available on-line and are ready to be used by TEFL and ELT teachers for teaching Listening, Speaking, Reading, Writing, Pronunciation, Grammar, etc. Some on-line English lessons may receive less attention from the students as the web pages are too complicated or the addresses are too difficult to be accessed. It can be caused by improper choice of learning template such as Moodle, Edmodo, the Blackboard system, etc or caused by type of application  used such as Wondershare, PPT Macros, Aurora 3D, Zondle, Hotpotato, iMindmap, Drop Box, Edmodo, ToolBook, Smashwords, Amazon Kindle DX, PowToon, and so forth. Therefore, it is critical to understand students’ continuous intention in following on-line English lessons. This study was aimed at assessing the influence of Perceived Usefulness and Ease of Use on Students’ Continuous Intention in learning on-line English Lessons. There were 230 pre-service English students (4A-4E classes) who took compulsory course of Teaching Media/ Instructional Technology during the academic year of 2016/2017.The students were divided into several groups for joining on-line English lessons of Listening, Speaking, Reading, Writing, Pronunciation, Grammar, Vocabulary, and TOEFL. While joining those on-line lessons, the researcher measured their continuous attention from ease-of-use, and perceived usefulness of extended Technology Acceptance Model (TAM). The data were collected through questioners and analysed by using Structural Equation Modelling (SEM).The results indicate that the students’ intentions are influenced positively by the design of the lessons, lessons delivery/ease-of-use, and their perceived usefulness. Perceived usefulness (PU) influenced more on students’ motivation than ease-of-use (PEOU). It is recommended that designers of on-line English lessons should consider students’ prior knowledge of ICT, pedagogical principles, and technological barrier in the students’ location for receiving more positive enduring intention.